Application of CRISPR/Cas9 in Alzheimer’s Disease - Lu, Likui; Yu, Xi; Cai, Yongle; Sun, Miao; Yang, Hao (Frontiers in Neuroscience, 2021)
Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative disorder clinically characterized by cognitive impairment, abnormal behavior, and social deficits, which is intimately linked with excessive β-amyloid (Aβ) protein deposition along with many other misfolded proteins, neurofibrillary tangles formed by hyperphosphorylated tau protein aggregates, and mitochondrial damage in neurons, leading to neuron loss. Currently, research on the pathological mechanism of AD has been elucidated for decades, still no effective treatment for this complex disease was developed, and the existing therapeutic strategies are extremely erratic, thereby leading to irreversible and progressive cognitive decline in AD patients. Due to gradually mental dyscapacitating of AD patients, AD not only brings serious physical and psychological suffering to patients themselves, but also imposes huge economic burdens to family and society. Accordingly, it is very imperative to recapitulate the progress of gene editing-based precision medicine in the emerging fields. In this review, we will mainly focus on the application of CRISPR/Cas9 technique in the fields of AD research and gene therapy, and summarize the application of CRISPR/Cas9 in the aspects of AD model construction, screening of pathogenic genes, and target therapy. Finally, the development of delivery systems, which is a major challenge that hinders the clinical application of CRISPR/Cas9 technology will also be discussed.